Chile : Accelerating e-Business for Small Business Innovation and Growth - Hanna, James (World Bank, Washington, DC, 2012)
Small businesses are important for employment creation and growth in Chile. They provide 73 percent of all private sector employment; half in micro-businesses (own account and firms employing fewer than 10 employees). But small business average growth was only 2.8 percent from 1994- 2000, less than half the 6.4 percent of large businesses. President Ricardo Lagos considers Chile's incorporation into the global and digital economy a top priority: "we are discovering that technology will enable us to surmount the geographical disadvantages of our nation. It is our obligation to take advantage of it to the fullest" (Inauguration speech, Santiago Times, November 24, 2000). The national strategy, "Chile: Toward the Information Society" lays out five key areas for digital development: technology infrastructure; community and business access; the legal framework for electronic transactions; education; and government services. Responding to this agenda, the World Bank's "Chile: Accelerating E-Business For Small Business Innovation and Growth" (November 2002) profiles Chile's small business sector, benchmarks e-business progress in Chile in relation to OECD countries, reviews public policies and programs emerging in Chile to promote e-business among small firms, and identifies some lessons from experience. Finally, it suggests measures that might accelerate and deepen e-business adoption in Chile. This work is a part of a larger forthcoming sector report by the Bank on Chile's new economy.